2017
DOI: 10.1007/s00384-017-2915-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative optimization of patients with inflammatory bowel disease undergoing gastrointestinal surgery: a systematic review

Abstract: Multimodel PO intervention in IBD patients is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 90 publications
0
49
0
7
Order By: Relevance
“…In line with this center’s standard of avoiding mechanical bowel preparation in CD patients, a review by Zangenberg et al. evaluated preoperative optimization strategies and concluded that “the evidence to support bowel preparation is not well established” and recommend avoiding bowel preparation until further data from ongoing studies are available [25]. In a recently published study by Iesalnieks et al.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this center’s standard of avoiding mechanical bowel preparation in CD patients, a review by Zangenberg et al. evaluated preoperative optimization strategies and concluded that “the evidence to support bowel preparation is not well established” and recommend avoiding bowel preparation until further data from ongoing studies are available [25]. In a recently published study by Iesalnieks et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is a crucial part of improving outcome. Steroid reduction, nutritional assessment and optimization, thrombosis prophylaxis, abscess drainage with antibiotics and smoking cessation are all components to this optimization .
…”
Section: Ileocaecal Resection In Crohn's Diseasementioning
confidence: 99%
“…In patients initially treated with a subtotal colectomy with an ileostomy, only one-third (680/ 2017) had their intestinal continuity restored [40]. Previous hospital-based studies have shown that 42-70% of patients undergo reconstructive surgery after colectomy [247,267] (49,50,54,86). Of those who do not undergo reconstruction the rate of subsequent proctectomy varies from 86% in older series to 18% in the era of pouch surgery.…”
Section: Subsequent Restorative Surgerymentioning
confidence: 99%
“…The optimal protocol for use of IBD therapies in the preoperative setting remains incompletely defined; however, several solid principles have emerged. Most importantly, steroids have a serious negative impact on postoperative outcomes [ 14 ]. In a meta-analysis by Subramanian et al [ 15 ], patients on steroids have an increased risk of all postoperative complications (infectious and noninfectious) that was dose related.…”
Section: Surgical Techniques and Perioperative Medical Managementmentioning
confidence: 99%